Development of Youth Creativity Through Malay Gift Arrangement Training at PKBM Insan Cendekia - Adelia Razis Putri; Seliana Maylani Nainggolan; Rafael Chasyanova; Rika Fitri Ramadani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Community education is one of the efforts to empower society through the development of skills that align with social and economic needs. The Malay gift arrangement training at PKBM Insan Cendekia is a program aimed at developing adolescents’ creativity while preserving local culture. This article discusses the development of creativity through the Malay Hantaran craft training program at PKBM Insan Cendekia. This study employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The research subjects consisted of PKBM managers, training tutors, and training participants. The results showed that the training was able to enhance participants’ creativity in producing hantaran products with aesthetic and commercial value. The level of participant involvement was very high, most participants passed the competency test, and most of the products created were considered marketable. Therefore, this training program not only contributes to the preservation of Malay culture but also helps improve participants’ skills and economic opportunities.